Online salafism - Zalta, Anja (Poligrafi, 2025)
Social networks and the digital competence of new generations create paral-lel spaces and search for new approaches in the religious sphere, which produce religious innovations based on alternative interpretations of traditional religious systems. This article highlights the example of Salafist online influencers who are shaping new dynamics among Muslim communities, including in Europe, and who often do not listen to the simultaneous consensus of all societal actors or do not participate (voluntarily or otherwise) in defining the basic principles or con-stitutive values of (European) societies. The aim of this article is to draw attention to the recognition of the diversification and dynamics within Muslim communi-ties in Europe today, with a particular focus on the rise of Salafi influencers who use social networks to spread their ideas and recruit followers. our thesis is that social networks and the digital literacy of the new generations (especially Genera-tion Z) create a parallel space that is alternative and often does not listen to the simultaneous consensus of all social actors. Salafist online influencers, who help shape the new dynamics between Muslim communities, including in Europe, of-ten increase the tensions within Muslim communities and with European society in a broader sense.
Keywords: digitalizacija; digitalization; družabna omrežja; Europe; Evropa; generacija Z; generation Z; muslimani; muslims; salafism; salafist influencers; salafizem; social networks; vplivneži